The Influence of Glycerol on Preparing Tapioca/TiO2 Bionanocomposite Films - Woradech Meedech; Natchayaporn Sakulpeeb; Sutee Chutipaijit; Wantana Koetniyom; Supamas Wirunchit (Thai Journal of Nanoscience and Nanotechnology, 2025)
This study focuses on the preparation of bionanocomposite films incorporating TiO2 nanoparticles synthesized through a green chemistry approach using extracts from sweet orange (Citrus sinensis) peels. Tapioca starch was used as the biopolymer matrix, while TiO2 nanoparticles served as the dispersed phase. The films were fabricated with varying glycerol-to-starch ratios (25%, 50%, 75%, and 100%) to determine the optimal formulation. Among these, the film containing 75% glycerol exhibited the most desirable mechanical and physical properties. The obtained films were subsequently characterized for their physical properties, water wettability via contact angle measurements, antibacterial activity using the disc diffusion method against Staphylococcus aureus and Escherichia coli, and biodegradability under sunlight exposure.
Keywords: Nanocomposite Films for Food Packaging; Nanoparticles: synthesis and applications; Advanced Cellulose Research Studies